Design, modeling, prototyping, and comparison of a low‐cost, small‐size, and accurate sensorless driver for switched reluctance motor. Issue 1 (27th December 2019) - Siadatan, Alireza; Torkaman, Hossein; Rafie, Mehran
Abstract: A switched reluctance motor (SRM) is a low‐cost motor with a simple structure and variable speed industrial and home applications. This article presents the design, simulation, and development of a low‐cost, accurate, and small‐size sensorless driver for a 6/4 three‐phase SRM. In the algorithm, the (nonlinear) relation of the flux, current, and rotor (FCR) position is linearized to achieve a modified FCR model, in which the values of the most important points of the primary FCR are emphasized. The SRM parameters required for the design process are obtained using a 3D finite‐element method (FEM). The proposed method is simulated and then tested under different load and speed conditions. The results are compared with a conventional sensorless algorithm's results, and the reference data are obtained by a direct with‐sensor algorithm. The algorithm estimates the rotor position (error of 1.3%) between low to nominal speed of the selected SRM under both nominal and no‐load conditions. In comparison with the conventional algorithm, the proposed FCR model significantly reduces the calculation cost and memory demand by 66%. Finally, the proposed algorithm decreases the driver size and price by 64% and 85%, respectively.